2012
DOI: 10.1371/journal.pone.0052104
|View full text |Cite
|
Sign up to set email alerts
|

The Mast Cell Degranulator Compound 48/80 Directly Activates Neurons

Abstract: BackgroundCompound 48/80 is widely used in animal and tissue models as a “selective” mast cell activator. With this study we demonstrate that compound 48/80 also directly activates enteric neurons and visceral afferents.Methodology/Principal FindingsWe used in vivo recordings from extrinsic intestinal afferents together with Ca++ imaging from primary cultures of DRG and nodose neurons. Enteric neuronal activation was examined by Ca++ and voltage sensitive dye imaging in isolated gut preparations and primary cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 30 publications
2
57
0
Order By: Relevance
“…Interestingly, c48/80 can function as a potent adjuvant, and evidence obtained using the so-called MC knockin approach in MC-deficient Kit W/W−v mice suggests that such an adjuvant effect is largely mediated by MCs (McLachlan et al, 2008) (see Section 3.1 for details about the use and potential limitations of the MC knockin model). However, c48/80 can also have direct effects on other cell types, as recently demonstrated for excitation of cultured enteric neurons (Schemann et al, 2012). …”
Section: Nongenetic Approaches For Analyzing the Functions Of Mastmentioning
confidence: 83%
“…Interestingly, c48/80 can function as a potent adjuvant, and evidence obtained using the so-called MC knockin approach in MC-deficient Kit W/W−v mice suggests that such an adjuvant effect is largely mediated by MCs (McLachlan et al, 2008) (see Section 3.1 for details about the use and potential limitations of the MC knockin model). However, c48/80 can also have direct effects on other cell types, as recently demonstrated for excitation of cultured enteric neurons (Schemann et al, 2012). …”
Section: Nongenetic Approaches For Analyzing the Functions Of Mastmentioning
confidence: 83%
“…Thus, either the intensity of response evoked by histamine released from C48/80 was higher than exogenous histamine when paralleled by the low availability of H2S released from GYY4137 in situ on the peripheral afferent neurons or it is possibly that C48/80 produces scratching behavior that somehow depends on functional changes evoked by direct activation of pruriceptors. While direct excitatory effects of C48/80 on dorsal root ganglion (DRG), enteric neurons and visceral afferents can occur independently of mast cell activation [54], other works show that the mechanism involved in C48/80-induced nociception is mediated by a cascade activation that starts after mast cell activation, including the release of mediators that can activate these nociceptors and promote pain [55].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that mast cells may thus play a modulatory role (17). In addition, compound 48/80 directly interacts with sensory nerves, potentially through Mrgprs (19). Since QWF antagonizes the interaction of compound 48/80 with Mrgprs, we examined the capacity of QWF to block compound 48/80-provoked itch.…”
Section: Qwf Is An Antagonist Of Compound 48/80-induced Mrgpr Activatmentioning
confidence: 99%